Polygenic Score Models for Alzheimer’s Disease: From Research to Clinical Applications - Zhou, Xiaopu; Li, Yolanda Y. T.; Fu, Amy K. Y.; Ip, Nancy Y. (Frontiers in Neuroscience, 2021)
The high prevalence of Alzheimer’s disease among the elderly population and its lack of effective treatments make this disease a critical threat to human health. Recent epidemiological and genetics studies have revealed the polygenic nature of the disease, which is possibly explainable by a polygenic score model that considers multiple genetic risks. Here, we systemically review the rationale and methods used to construct polygenic score models for studying Alzheimer’s disease and discuss the associations of polygenic risk scores with clinical outcomes, brain imaging findings, and biochemical biomarkers from both the brain and peripheral system. We also discuss the possibility of incorporating polygenic score models into research and clinical practice along with potential challenges.